(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2018)
In this paper, studying synthesis zinc oxide nanoparticles (ZnO NPs) via sol - gel methodand effect of adding polymer in preparation its solution. Zinc nitrate hexahydrate,Polyvinylpyrrolidone PVP, distilled water and sodium hydroxide (NaOH) were used asprecursor materials. Crystallization behavior of the ZnO was studied by X-ray diffraction(XRD). Nanoparticles phases can change from amorphous to wurtzite structure at thecalcination temperature (500 °C) and crystallite size by Scherrer’s formula about (21.131)nm for samples prepared with distilled water and (20.035)nm for samples prepared withdissolved PVP. Morphological and structural properties were investigated by scanningelectron microscopy (SEM). FT-IR spectra was indicated characteristic absorption bands ofZnO. UV-Vis absorption spectrum was shown a typical spectrum for ZnO nanoparticles.Finally, the results were shown the samples with dissolved PVP has smaller particles size,less agglomeration and narrow distribution but less purity phase when compared withsamples prepared with distilled water.